Career Planning, Individual's Personality Traits, HRM Practices as Determinants to Individual Career Success: The Role of Career Strategies as Mediator - Tan, Fee Yean (2010)
The main objective of this study is to examine the predictors of individual's career success. Based on the Social Cognitive Career Theory (SCCT), Gould's career planning model, and goal-setting theory, this study reveals that there is a relationship between career planning, individual's personality traits, HRM practices and career success. The two dimensions that measure career planning are awareness of self and environment, and goal-setting. Individual's personality traits consist of five dimensions namely; neuroticism, agreeableness, openness to experience, extraversion and conscientiousness. The three dimensions that measure HRM practices are; compensation, performance appraisal, and training and development, while career strategies comprise of five dimensions namely;interpersonal attraction, seeking social support, self-nomination, creating opportunities and extended work involvement. Lastly, the dimension that measure career success is subjective career success. Data was gathered through questionnaire survey of insurance agents (n = 531) located in the northern states of peninsular Malaysia. Hierarchical Multiple Regression Analysis (HMRA) was used to examine (1) the relationship between career planning, individual's personality traits, HRM practices and career strategies; (2) the relationship between career planning, individual's personality traits, HRM practices, career strategies and career success; and (3) the mediating role of career strategies on the relationship between career planning, individual's personality traits, HRM practices and career success. The results indicated that most of the hypotheses were partially supported. Additionally, the following variables were related to career strategies' dimensions (1) awareness of self and environment, (2) goal-setting, (3) extraversion, (4) agreeableness, (5) conscientiousness, (6) training and development, (7) performance appraisal, and (8) compensation. The results of this study also indicated that career planning (awareness of self and environment, and goal-setting), individual's personality traits (extraversion), HRM practices (training and development, and compensation), and career strategies (interpersonal attraction, seeking social support and self-nomination) were correlated with career success. This study also examined the role of career strategies as mediators of the relationship between career planning, individual's personality traits, HRM practices and career success. Results provided partial support for the mediating role of career strategies (interpersonal attraction, seeking social support and self-nomination) on the relationship between career planning (awareness of self and environment, and goal-setting), individual's personality traits (extraversion), HRM practices (training and development, and compensation) and career success. Overall, this study provided support to the proposition of Social Cognitive Career Theory (SCCT) and Gould's career planning model, and filled the research gaps, particularly about the mediating role of career strategies. The results offered several hints to the employees regarding the potential factors that may affect their efforts to achieve career success, and also provided some insights into the present HR practitioners in formulating strategies to increase employees' career success. The limitations of the study and recommendations for future research were also satisfactorily addressed.